Why Is Corporate Tax Revenue Stable While Tax Rates Fall? Evidence from Firm-Level Data - Clemens Fuest; Felix Hugger; Susanne Wildgruber (Center for Economic Studies and Ifo Institute (CESifo), 2020)
While corporate tax rates in OECD countries declined over the last decades, revenues from corporate taxation relative to GDP remained remarkably stable. This paper uses a comprehensive firm-level dataset to provide an explanation for this rate-revenue puzzle in corporate taxation. Focusing on the period 1995-2016, we show that the reduction in corporate tax rates was counterbalanced by a pronounced increase in corporate profits before taxes. We decompose the rise in profits into changes in EBITDA, depreciation, and financial profits. On average, these three factors contributed almost equally to the tax base expansion, albeit differently across sectors, countries, and firm sizes.
Keywords: H25; 330; corporate income taxation; corporate tax revenues; corporate profitability